A Study on Visual, Audio and Tactile Reaction Time among Medical Students at Kampala International University in Uganda - Kasozi, Keneth Iceland; Namubiru, Sarah; Safiriyu, Abass Alao; Okpanachi, Alfred O; Ninsiima, Herbert Izo (African health sciences, 2018)
Reaction time (RT) is an indicator of neural activity, however, its variation due to visual (VRT), audio (ART) and tactile (TRT) in African medical students has not been investigated. The aim of the study was to determine relationships between VRT, ART and TRT amongst medical students in Uganda.This was a cross sectional study, the body mass index (BMI) and RT (i.e. VRT, ART and TRT) were determined using weighing scale with standiometer and the catch a ruler experiment respectively. A questionnaire was administered to collect information on participant’s lifestyle patterns and analysis was done using SPSS Version 20. The mean (± SEM) VRT, ART and TRT in the study were found to be 0.148 ± 0.002s, 0.141 ± 0.002s and 0.139 ± 0.003s respectively. A strong correlation between TRT and ART was found to exist in the youthful Ugandan medical student’s population. Furthermore, significant differences in ART and VRT were observed with sex, although these were absent amongst preclinical and clinical students, showing the importance of sex in RT. The low VRT and ART in Ugandan medical students is indicative of a healthy somatosensory connectivity, thus of academic importance.
Keywords: Reaction time, cognitive performance, neural health, medical education.